Transformasi Sistem Pendidikan dari Masa Kolonial Belanda hingga Pendidikan Indonesia Masa Kini: Sebuah Tinjauan Historis - SOIM (Institut Agama Islam Pangeran Diponegoro Nganjuk, 2026)
ABSTRACT The Indonesian education system has experienced substantial changes from the period of Dutch colonial rule to the contemporary era. During the colonial period, educational access was highly restricted and primarily intended for European communities and indigenous elites, resulting in social stratification and unequal educational opportunities. In contrast, the current Indonesian education system is founded on the principles of equity, inclusiveness, and the holistic development of learners. This study aims to analyze and compare the characteristics, objectives, and implications of the Dutch colonial education system and the contemporary Indonesian education system from a historical perspective. Employing a qualitative literature review approach, this research examines relevant historical records, scholarly publications, and educational policy documents. The findings reveal that colonial education functioned mainly as an instrument to support the political, administrative, and economic interests of the Dutch government, whereas modern Indonesian education is oriented toward democratization, equal access, character formation, and the enhancement of human resources. The study underscores the importance of understanding historical educational developments as a foundation for formulating educational policies that are responsive to societal needs, equitable, and capable of meeting global challenges. Keywords: Dutch Colonial Education, Indonesian Education System, Historical Comparison, Educational Transformation